Death from below: Investigation of inhibitory factors in bloom development during a wastewater effluent diversion. (15th February 2017) - Kudela, Raphael M.; Lucas, Andrew J.; Hayashi, Kendra; Howard, Meredith; McLaughlin, Karen
Abstract: Eutrophication of coastal waters is an urgent and globally increasing problem. A significant source of nutrients to Southern California coastal waters is direct discharge of secondarily treated wastewater effluent from regional Publicly Owned Treatment Works. The planned diversion of treated wastewater from the Orange County Sanitation District's main (5-mile) pipe to a shallow 1-mile pipe off Huntington Beach, CA in autumn 2012 provided an unprecedented opportunity to monitor the response of the coastal phytoplankton community to a major anthropogenic loading event. Despite the continuous release of approximately 11.07 × 10 6  m 3 of effluent containing 1743 μM ammonium, there was virtually no detectable change in phytoplankton biomass, in striking contrast to the harmful algal bloom dominated community that quickly developed in response to a comparable diversion in Santa Monica Bay in 2006. Field and laboratory studies demonstrate that disinfection byproducts associated with enhanced dechlorination were present in the discharged water, and that these compounds had a strong inhibitory impact on phytoplankton photophysiology and growth, lasting 24 h for photosynthetic performance and at least 3 d for growth, assessed as change in chlorophyll. Thus, the perhaps fortuitous unintended consequence of enhanced chlorination was the production of inhibitory compounds that suppressed the potential phytoplankton response over a large swath of the continental shelf during the diversion. Highlights: Phytoplankton response to a deliberate wastewater effluent diversion was documented. Lack of response is attributed to production of disinfection byproducts. Inhibition of phytoplankton photosynthesis and growth occurs for at least 24–72 h. Ammonium inhibition of phytoplankton growth is not evident.